2003
DOI: 10.1002/pola.10704
|View full text |Cite
|
Sign up to set email alerts
|

Copolymerization of α‐terpineol with styrene: Synthesis and characterization

Abstract: Radical copolymerization of ␣-terpineol with styrene (Sty) initiated by azobisisobutyronitrile in xylene at 80 Ϯ 0.1°C for 2 h followed ideal kinetics and resulted in the formation of a functional and alternating copolymer as evidenced by spectral analysis. The activation energy was 28 kJ/mol. ␣-Terpineol underwent copolymerization as well as a chain-transfer reaction. The values of the monomer reactivity ratios calculated by the Kelen-Tü dos method were r 1 (Sty) ϭ 0.033 and r 2 (␣-terpineol) ϭ 0.004. The Alf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 12 publications
(9 reference statements)
0
14
0
Order By: Relevance
“…12-14 Furthermore, the work has been emphasized by recent contributions of our laboratory, which has obtained optically active and functional polymers of cyclic/acyclic terpenes with different vinyl monomers, such as citronellol-costyrene/tetraphenyl cyclopentadiene Arsoniumylide and citronellol-co-styrene/benzoyl peroxide (BPO) at 808C, 15 citronellol-co-acrylonitrile/BPO at 758C, 16 geraniol-co-styrene/BPO at 808C, 17 linalool-co-acrylonitrile/BPO at 758C, 18 a-terpineol-co-methyl methacrylate, 19 a-terpineol-co-styrene/BPO at 808C, 20 limonene-co-acrylonitrile/BPO at 708C, 21 limonene-comethyl methacrylate/BPO at 808C, 22 and limonene-costyrene/azobisisobutyronitrile (AIBN) at 808C. 23 Limonene (Lim), an optically active monocyclic terpene, is a constituent of citrus and orange fruits.…”
Section: Introductionmentioning
confidence: 99%
“…12-14 Furthermore, the work has been emphasized by recent contributions of our laboratory, which has obtained optically active and functional polymers of cyclic/acyclic terpenes with different vinyl monomers, such as citronellol-costyrene/tetraphenyl cyclopentadiene Arsoniumylide and citronellol-co-styrene/benzoyl peroxide (BPO) at 808C, 15 citronellol-co-acrylonitrile/BPO at 758C, 16 geraniol-co-styrene/BPO at 808C, 17 linalool-co-acrylonitrile/BPO at 758C, 18 a-terpineol-co-methyl methacrylate, 19 a-terpineol-co-styrene/BPO at 808C, 20 limonene-co-acrylonitrile/BPO at 708C, 21 limonene-comethyl methacrylate/BPO at 808C, 22 and limonene-costyrene/azobisisobutyronitrile (AIBN) at 808C. 23 Limonene (Lim), an optically active monocyclic terpene, is a constituent of citrus and orange fruits.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis and characteristics of the copolymer of ␣-terpineol with styrene was reported elsewhere. 34 Briefly, a solution in xylene containing ␣-terpineol (0.730 mol/L), styrene (1.51 mol/L), and AIBN (7.6 ϫ 10 -3 mol/L) as the initiator was polymerized for 2 h at 80 Ϯ 0.1°C under an inert atmosphere of nitrogen. The copolymer was precipitated in acidified methanol and dried to a constant weight.…”
Section: Synthesis Of the Copolymermentioning
confidence: 99%
“…Characterization of the ␣-terpineol-co-styrene copolymer 34 Ir spectroscopy 34 The IR spectrum of the copolymer (Fig. 1) showed the following group of bands:…”
Section: Synthesis Of the Copolymermentioning
confidence: 99%
“…It has been observed that oxygenated derivatives of terpenes generally do not undergo homo-polymerization due to steric hindrance [7], low stabilization energy between monomer and free radicals in the transition state [8], excessive chain transfer [9] and termination of cyclization as in the case of 1,2-disubstituted ethylene [10]. Thus, the literature is almost devoid of radical polymerization of acyclic/cyclic terpenes with vinyl monomers, except few recent contributions from our laboratory, e.g., citronellol-co-styrene [11], citronellol-covinylacetate [12], citronellol-co-acrylonitrile [13], linalool-co-acrylonitrile [14], linalool-co-styrene [15], α-terpineol-co-methylmethacrylate [16], α-terpineol-costyrene [17], limonene-co-styrene [18] and limonene-co-acrylonitrile [19]. These terpenoids are useful as novel monomers and have great relevance because they yield optically active and functional co-polymers.…”
Section: Introductionmentioning
confidence: 99%